Single-molecule DNA biosensors for protein and ligand detection. - Lymperopoulos, K; Crawford, R; Torella, J; Heilemann, M; Hwang, L; Holden, S; Kapanidis, A (2010)
(Chemical Equation Presented) Transcription factors (TFs) control gene expression and are promising biomarkers for diseases. In a new, robust, and sensitive single-molecule fluorescence assay TFs and associated small molecules (such as nucleotides and sugars) are detected based on DNA coincidence of the two halves of the binding site (see picture; S = stoichiometry). The assay is compatible with measurements in solution, on solid supports, and even in complex biological samples. © 2010 Wiley-VCH Verlag GmbH and Co. KGaA.